Challenges and Opportunities of Waste Collection in Caracas: Sucre Municipality Case Study - Ramos, Camille; Vicentini, Adriana; Ortega, Daniela (Consilience, 2012)
This paper provides an overview of solid waste management by local authorities in the Sucre municipality in Caracas, Venezuela. Sucre is currently faced with serious demographic, economic, social, urban, and administrative challenges in solid waste management. The municipality, called Petare, has one of the largest slums in Latin America. It is estimated that more than a million people live in Petare, and 30% live in poverty. Venezuela is also facing a political problem that has affected the solid waste management throughout the country. Local authorities in Sucre have worked with communities to develop solutions to confront these difficulties.